First separation of four aromatic acids and two analogues with similar structures and polarities from Clematis akebioides by high‐speed counter‐current chromatography. Issue 23 (9th November 2016) - Gong, Chengcheng; Chen, Tao; Chen, Huifeng; Zhang, Shanshan; Wang, Xinzhu; Wang, Weiqing; Sun, Jing; Li, Yulin; Liao, Zhixin
Abstract : In this paper, we report an efficient method by high‐speed counter‐current chromatography for the first separation of four aromatic acids and two analogs with similar structures and polarities from Clematis akebioides . First, the ethyl acetate extract was treated by silica gel column chromatography to enrich the target compounds. And then the fraction with target compounds were purified by high‐speed counter‐counter chromatography using a two‐phase solvent system consisting of chloroform/acetonitrile/water (10:6:4, v/v). The results showed high‐speed counter‐current chromatography could be a powerful technology for the separation of compounds with similar structures and polarities. Besides, it was found acetonitrile could be a good methanol substitute when a chloroform/methanol/water system could not provide a good separation factor. This study provides a reference for the separation of compounds from Clematis akebioides .